2017
DOI: 10.17352/2581-4265.000020
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Views on Their Profession in Turkey and Influencing Factors

Abstract: Objective: The study was conducted as a descriptive and cross-sectional to determine nurses' views on their profession in Turkey, their commitment to the profession and participation in professional activities and infl uencing factors. Methods: The study sample comprised 2253 nurses working in hospital in Turkey. The data were collected using a questionnaire developed by the researchers. For the assessment of the data, percentages, the chi square and multiple logistic regression analysis were used. Results: Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The reviewed articles showed that career identity is certainly linked to job-related satisfaction amongst medical and surgical nursing professionals in a total of 28 national healthcare settings as well as 14 university health organizations in seven regions across Turkey [38]. It was also found that professionalism was correlated with work-related satisfaction amongst medical/surgical nurses across Turkey [39,40].…”
Section: Intrinsic Factors Impacting Job-related Satisfactionmentioning
confidence: 99%
“…The reviewed articles showed that career identity is certainly linked to job-related satisfaction amongst medical and surgical nursing professionals in a total of 28 national healthcare settings as well as 14 university health organizations in seven regions across Turkey [38]. It was also found that professionalism was correlated with work-related satisfaction amongst medical/surgical nurses across Turkey [39,40].…”
Section: Intrinsic Factors Impacting Job-related Satisfactionmentioning
confidence: 99%